A natural diarylheptanoid promotes neuronal differentiation via activating ERK and PI3K-Akt dependent pathways. (10th September 2015) - Tang, G.; Dong, X.; Huang, X.; Huang, X.-J.; Liu, H.; Wang, Y.; Ye, W.-C.; Shi, L.
Highlights: Three natural diarylheptanoids possessed neurogenic and neuritogenic activities. Cpd 1 promoted differentiation of neuroblastoma cells and hippocampal neurons. Cpd 1 promoted differentiation/maturation of adult-born dentate neural progenitors. Pro-differentiation activity of Cpd 1 was dependent on ERK and PI3K-Akt pathways. Abstract: Neuronal differentiation is a critical developmental process that determines accurate synaptic connection and circuit wiring. A wide variety of naturally occurring compounds have been shown as promising drug leads for the generation and differentiation of neurons. Here we report that a diarylheptanoid from the plant Alpinia officinarum, 7-(4-hydroxyphenyl)-1-phenyl-4 E -hepten-3-one (Cpd 1), exhibited potent activities in neuronal differentiation and neurite outgrowth. Cpd 1 induced differentiation of neuroblastoma Neuro-2a cells into a neuron-like morphology, and accelerated the establishment of axon-dendrite polarization of cultured hippocampal neurons. Moreover, Cpd 1 promoted neurite extension in both Neuro-2a cells and neurons. We showed that the effects of Cpd 1 on neuronal differentiation and neurite growth were specifically dependent on the activation of extracellular signal-regulated kinases (ERKs) and phosphoinositide 3-kinase (PI3K)-Akt signaling pathways. Importantly, intraperitoneal administration of Cpd 1 promoted the differentiation of new-born progenitor cells into mature neurons in the adult hippocampal dentate gyrus. Collectively, this study identifies a naturally occurring diarylheptanoid with beneficial effects on neuronal differentiation and neurite outgrowth in vitro and in vivo .